Analisis Perbandingan Kinerja Investasi Portofolio Pasar Modal Syariah Dengan Pasar Modal Konvensional (Studi Kasus Pada Jakarta Islamic Index dan IDX30) - Siti Wardani Bakri Katti; Mutmainah Mutmainah (Universitas Merdeka Madiun, 2020)
Abstract— The general difference between conventional capital markets and Islamic capital markets can see in the instruments and transactio mechanism, while the difference of Sharia stock index value with conventional stock index value lies in the criteria of the issuer’s shares that must meet the basic principles of sharia. The aim of this research is 1) to know average difference of return between Jakarta Islamic Index (JII) with IDX30 in bullish and bearish period, 2) to know the difference of return between Jakarta Islamic Index (JII) with IDX30 in bullish and bearish period through Sharpe Index approach. The research type is explanatory research. This research use all of go public companies on Indonesia Stock Exchange (BEI) from 2014-2018. Sampling in this research use purposive sampling. The classic assumption test uses normality and homogeneity test. Data analysis method use independent sample T-test. The research result show that no average difference of return of portfolio investment performance in the 2014-2018 period between Jakarta Islamic Index (JII) with IDX30 in the bullish and bearish period. Portfolio investment performance in the 2014-2018 period show no average difference of return between Jakarta Islamic Index (JII) with IDX30 through Sharpe index approach in the bullish and bearish period. Keywords—: Islamic Capital Markets; Conventional Capital Markets; Jakarta Islamic Index; IDX30; Indonesia Stock Exchange.